Measuring the shadow economy: Endogenous switching regression with unobserved separation - Tomáš Lichard; Jan Hanousek; Randall Keith Filer (Institute for the Study of Labor (IZA), 2012)
We develop an estimator of unreported income, perhaps due to tax evasion, that does not depend on as strict identifying assumptions as previous estimators based on microeconomic data. The standard identifying assumption that the self-employed underreport income whereas wage and salary workers do not is likely to fail in countries where employees are often paid under the table or engage in corrupt activities. Assuming that evading individuals have a higher consumption-income gap than non-evading ones due underreporting both to tax authorities and in surveys, an endogenous switching model with unknown sample separation enables the estimation of consumption-income gaps for both underreporting and truthful households. This avoids the need to identify non-evading and evading groups ex-ante. This methodology is applied to data from Czech and Slovak household budget surveys and shows that estimated evasion is substantially higher than found using previous methodologies.
Keywords: C34; E01; H26; J39; 330; shadow economy; switch regression; income-consumption gap; Schattenwirtschaft; Steuerkriminalität; Schätztheorie; Einkommen; Verbraucherausgaben; Schätzung; Tschechische Republik; Slowakei